Green Synthesis of Ag/Chitosan Nanoparticles using Avocado Leaves Bioreductor (Persea americana Mill.) as a Nitrite Colorimetry Detector - Lestari, Nani; Puspitasari, Ratih Dyah Puspitasari; Susanto, Nindita Clourisa Amaris; Tarigan, Indra Lasmana; Nelson, Nelson (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Urinary tract infection (UTI) is one of the most common types of infection caused by the growth of microorganisms in the human urinary tract. Nitrite can be detected using spectroscopy, electrochemistry, chemiluminescence, chromatography, capillary electrophoresis, and flow injection analysis methods. However, this method takes quite a long time. So, this method is not suitable for rapid screening because it requires time for bacterial incubation and adequate sample preparation. So, there is a need for a fast-screening method that can diagnose UTIs through a nitrite colorimetric sensor. The colorimetric method is based on nanoparticles, which are relatively cheap and can provide visual and rapid detection. Nitrite is an indicator in diagnosing UTI. This research aims to determine the synthesis of Ag nanoparticles using avocado leaf bio-reductors (Persea americana Mill.) and chitosan as a stabilizer, which can be used as a colorimetric nitrite detector to minimize the use of dangerous and environmentally unfriendly inorganic materials. Characterization and analysis in this research used a UV-Vis spectrophotometer, FT-IR (Fourier Transform Infra-Red), and PSA (Particle Size Analyzer). The Ag nanoparticle synthesis process was carried out by varying the bioreductant volume, synthesis time, and chitosan concentration. It was found that the optimum synthesis time was 4 hours with an SPR value of 428 nm, an absorbance of 2.112 and a nanoparticle size. Apart from that, the optimum concentration of chitosan was obtained at a concentration of 2.5% with an SPR of 435 nm and an absorbance of 1.341 with a nanoparticle size. The results obtained from AgNPs/chitosan as a colorimetric nitrite detector showed a color change to purple with an LOD value of 0.1303 µM and an LOQ of 0.4345 µM. Keywords: Ag Nanoparticles; Avocado Leaveas; Colorimetry; Nitrite.